The Study of EFL Students’ Anxiety in Public Speaking Performance at SMK Assa’adah Gresik - Lailatul Rohmah; Dina Amaliyah Mushthoza (Mathematics Education Study Program, 2025)
Many Indonesian EFL learners show anxiety when speaking English. Therefore, the researcher interests to conduct this research to find out the level of English-speaking anxiety performance. This research aims to investigate speaking anxiety of English Community students at SMK Assa’adah Gresik. Specifically, the researcher attempts to identify what are the factors that may contribute to anxiety in public speaking performance environment based on students' perspective and to investigate the level of students’ anxiety in public speaking performance. The method used in this study is descriptive qualitative method. The data are gathered through observation checklist, questionnaire, and interview. The most commonly used tool for assessing FLA is the FLCAS (Foreign Language Classroom Anxiety Scale) developed by Horwitz et al. (1986). A modified version of FLCAS was used in this study. The original version of FLCAS is a point scale instrument ranged from (strongly disagree to strongly agree) measuring students language anxiety.